2022
DOI: 10.3389/fphar.2022.1005011
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive comparison on the anti-inflammation and GC-MS-based metabolomics discrimination between Bupleuri chinense DC. and B. scorzonerifolium Willd

Abstract: Bupleuri Radix (BR) is a traditional Chinese medicine and widely used for cold and fever, influenza, inflammation, hepatitis and menstrual diseases. Two authentic medicinal plants of Bupleuri chinense DC. (Beichaihu, BCH) and B. scorzonerifolium Willd. (Nanchiahu, NCH) are recommended by the current Chinese Pharmacopoeia for BR. In the present study, the comparative investigations on the anti-inflammatory effects and gas chromatography-mass spectrometry (GC-MS)-based metabolomics for the species discrimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…However, this essential oil was inactive against Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), and Salmonella enterica (ATCC 13076) as previously reported (18). Chromatography-based untargeted metabolomics studies are quick-to-use and reliable approaches, and they have been used for quality studies on herbal medications recently (19,20). Among the major phytochemicals detected (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…However, this essential oil was inactive against Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), and Salmonella enterica (ATCC 13076) as previously reported (18). Chromatography-based untargeted metabolomics studies are quick-to-use and reliable approaches, and they have been used for quality studies on herbal medications recently (19,20). Among the major phytochemicals detected (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…It was reported that volatile oil of BSW had stronger anti‐inflammatory effect than that of BCD, [18] which furthered the potential benefits of BSW utilization. Fever is a typical symptom accompanied with inflammatory diseases [19] .…”
Section: Resultsmentioning
confidence: 94%
“…GC-MS could provide the highest resolution for the separation of compounds with less method development, as a single gaseous mobile phase is used with a temperature gradient. Furthermore, GC-MS with electron impact ionization provides a fingerprint of the primary and secondary metabolites, making GC-MS an indispensable tool in mixture analysis [72,73]. Selective extraction followed by the characterization of secondary metabolites with the help of sophisticated instruments is highly important in identifying the active principles in plant-derived extracts.…”
Section: Discussionmentioning
confidence: 99%